Stars and Water Carriers ; The Impossible Hour - Leth, Jorgen; Holmberg, Dan; Penazzo, Sergio; Berasaluce, J. M. (Danish Film Institute, 2007)
Stars and Water Carriers (1974): Jørgen Leth made a film about the international cycle race Giro d’Italia - without hiding the financial interests behind it - which appears to defend the idolisation of professional sports. In Leth’s own words, "I regard the world of sports as classical theatre whose heroes evoke classicals virtues, like those of mythology, and do legendary performances. This is the object of my praise and study". Belgian Eddy Merckx is the film’s real principal character, but the film also focuses on the time trial of the legendary Danish cyclist, Ole Ritter. [Beiheft]
Keywords: DVD-Video